Pharmacogenomics- The Promise of Personalized Medicine - Fakruddin, M; Chowdhury, A (Bangladesh Journal of Medical Science, 2013)
Introduction: Pharmacogenomics (PGx) is the study of the genetic basis of variability among individuals in response to drugs. It is the newest discipline of medicine and is becoming a very active area of research, with the pharmaceutical industry gaining experience applying it, integrating it into the drug development process, and also learning to better manage the expectations of the medical community. Methodology: A comprehensive review of the literature on the principles, applications, challenges and prospects of pharmacogenomics was performed. Results: Pharmacogenomics tailors therapies to the genetic makeup of an individual and can therefore offer treatments that are more efficacious and have fewer side effects. Despite these benefits, personalized medicine has not been embraced by large pharmaceutical companies. It is expected that the first wave of successful pharmacogenomics products will be used in acute treatments for which current therapies have and severe side effects. These products should also be good candidates for premium pricing. Personalized medicine (PM), based on the genetic makeup of a patient, may result in not only an improved therapeutic response but also a clinically important reduction in adverse drug reactions. The experience to date is mixed, with a few successes but many frustrations. Conclusion: However, for pharmacogenomics to be truly embraced, the benefits of this technology must become more widely accepted in terms of economic, public, regulatory and ethical issues. DOI: http://dx.doi.org/10.3329/bjms.v12i4.11041 Bangladesh Journal of Medical Science Vol. 12 No. 04 October 13 Page 346-356